2013
DOI: 10.3109/19396368.2013.796021
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to fluoxetine via placenta and lactation inhibits the testicular development in male rat offspring

Abstract: Due to the widespread use of fluoxetine to treat depression, including pregnant and nursing women, the present study aimed to investigate the effects of in utero and lactational exposure to fluoxetine in rat offspring at post natal day 22. Wistar rat dams were orally treated with fluoxetine (5, 10, and 20 mg/kg) from day 13 gestation to day 21 lactation. Exposure to 10 and 20 mg/kg fluoxetine reduced the body and testis weights. The volume of the seminiferous tubules and epithelium were also reduced following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
(38 reference statements)
0
13
0
2
Order By: Relevance
“…In the present study we have shown that fetal and neonatal exposure to fluoxetine resulted in a significant increase in body weight in the female but not in the male offspring; these changes occurred in the absence of altered postnatal food consumption despite the fact that fluoxetine has been shown to affect food consumption in adult rodents (Lauzurica et al, 2013). Moreover, although other experiments in rats have reported a reduction in birth weight following fluoxetine exposure during pregnancy (de Oliveira et al, 2013;Müller et al, 2013) we did not observe any effect of fluoxetine in altering birth weight in our study, suggesting that the metabolic deficits in this model are independent of impaired fetal growth. Although the mechanism(s) underlying the sex-specific differences in body composition are unknown, sex-specific differences in the long-term effects of prenatal exposure to SSRIs and childhood overweight have also been reported in human studies (Grzeskowiak et al, 2013).…”
Section: Discussionmentioning
confidence: 48%
“…In the present study we have shown that fetal and neonatal exposure to fluoxetine resulted in a significant increase in body weight in the female but not in the male offspring; these changes occurred in the absence of altered postnatal food consumption despite the fact that fluoxetine has been shown to affect food consumption in adult rodents (Lauzurica et al, 2013). Moreover, although other experiments in rats have reported a reduction in birth weight following fluoxetine exposure during pregnancy (de Oliveira et al, 2013;Müller et al, 2013) we did not observe any effect of fluoxetine in altering birth weight in our study, suggesting that the metabolic deficits in this model are independent of impaired fetal growth. Although the mechanism(s) underlying the sex-specific differences in body composition are unknown, sex-specific differences in the long-term effects of prenatal exposure to SSRIs and childhood overweight have also been reported in human studies (Grzeskowiak et al, 2013).…”
Section: Discussionmentioning
confidence: 48%
“…The reduction in these parameters shown in our study also indicates a reduction in fertility after exposure to fluoxetine. Oliveira et al [2013] also observed a reduced volume of seminiferous tubules and epithelium after exposure to fluoxetine at 20 mg/kg via placenta and lactation. Moreover, germ cells and Sertoli cells are located in seminiferous epithelium [Holstein et al 2003], considering that the population of Sertoli cells did not change, the present study also indicates an effect of fluoxetine on germ cells.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies published by our research group showed a reduction in the Sertoli cell population after intraperitoneal treatment with fluoxetine 5, 10, and 20 mg/kg [Silva Junior et al 2008] and exposure to 20 mg/kg fluoxetine via the placenta and lactation [Oliveira et al 2013] in young animals. However, in the present study and according to Silva Junior et al [2013], the Sertoli cell population in adulthood did not change after perinatal exposure to fluoxetine.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations